2021
DOI: 10.1007/s00431-021-04281-y
|View full text |Cite
|
Sign up to set email alerts
|

Delta neutrophil index and C-reactive protein: a potential diagnostic marker of multisystem inflammatory syndrome in children (MIS-C) with COVID-19

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a life-threatening hyperinflammation syndrome emerging after COVID-19. The serum delta neutrophil index (DNI) reflects the fraction of circulating immature granulocytes and is evaluated in infection and inflammation. The aim of this study is to evaluate the usefulness of DNI as a diagnostic marker in patients with MIS-C and to assess its role in determining the severity of MIS-C. This retrospective, observational study included 83 patients with MIS-C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Recently it has been claimed that CRP is the excellent diagnostic of inflammatory biomarkers in children with COVID-19 that suffered from the multisystem inflammatory syndrome. 50 Another study found an association between an elevated level of D-dimer, which is considered a coagulation biomarker and an increased mortality rate in COVID-19. Soni et al 51 and our data support these claims.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been claimed that CRP is the excellent diagnostic of inflammatory biomarkers in children with COVID-19 that suffered from the multisystem inflammatory syndrome. 50 Another study found an association between an elevated level of D-dimer, which is considered a coagulation biomarker and an increased mortality rate in COVID-19. Soni et al 51 and our data support these claims.…”
Section: Discussionmentioning
confidence: 99%
“…Birben et al ( 29 ), in their study on 388 patients with COVID-19 requiring intensive care, concluded that the DNI could be used as an effective prognostic biomarker for mortality in these patients. Moreover, according to the study by Karagol et al ( 30 ), there was a statistically significant association between the DNI levels and the severity of multisystem inflammatory syndrome in children with COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…DNI is a reflection of the rate of immature granulocytes in the serum, and in recent years, the change in DNI in conditions of infection and inflammation has become the subject of many studies (8)(9)(10). Although there are several studies related to inflammation and sepsis, there are very few studies that have researched the relationship with COVID-19 (12,13). In a study by Karabel et al (12), the DNI values were compared in patients with multisystem inflammatory syndrome in children (MIS-C), COVID-19, and control group paediatric patients, and the highest DNI values were determined in the MIS-C group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies related to inflammation and sepsis, there are very few studies that have researched the relationship with COVID-19 (12,13). In a study by Karabel et al (12), the DNI values were compared in patients with multisystem inflammatory syndrome in children (MIS-C), COVID-19, and control group paediatric patients, and the highest DNI values were determined in the MIS-C group (p<0.001). It was also determined that the DNI levels increased together with disease severity in the MIS-C group.…”
Section: Discussionmentioning
confidence: 99%